ANTIBACTERIAL PROPERTIES OF SELECTED MEDICINAL PLANTS AGAINST PATHOGENIC BACTERIA (International Journal of Scientific Research and Management (IJSRM), 2014)
Plants are rich source of antibacterial agents, which could be exploited in human disease management.The present investigation focused on antibacterial activity of Acacia nilotica, Catharanthus roseus, Sida cordifolia, Euphorbia hirta against four bacterial pathogen among which three were gram negative (Escherichia coli, Pseudomonasaeruginosa, Enterococcoous faecalis) and one was gram positive (Staphylococcus aureus).The antibacterial activities of Methanol, ethanol and acetone extract of four medicinal plants,Acacia nilotica, Catharanthus roseus, Sida cordifolia ,Euphorbia hirta were evaluated by using agar well diffusion method against four bacterial pathogen with measurement of minimum inhibitory concentration of these plants.From the result obtained Acacia nilotica, Catharanthus roseus, Sida cordifolia and Euphorbia hirta showed potent antibacterial activity against selected bacterial pathogens. Methanol extract of these medicinal plants exhibit greater inhibitory effect over the micro organisms.